An unprecedented 1, 4-diphospha-2, 3-disila butadiene (–PSi–SiP–) derivative and a 1, 3-diphospha-2-silaallyl anion, each stabilized by the amidinate ligand. Issue 1 (5th December 2016) - Kundu, Subrata; Mohapatra, Chandrajeet; Samuel, Prinson P.; Kretsch, Johannes; Walawalkar, M. G.; Herbst-Irmer, Regine; Stalke, Dietmar; De, Sriman; Koley, Debasis; Roesky, Herbert W.
Abstract : The synthesis of a 1, 4-bisphosphino-2, 3-disila butadiene and a 1, 3-diphospha-2-silaallyl anion has been reported. Abstract : The first acyclic 4π-electron –PSi–SiP– motif with two four coordinate silicon substituents supported by the amidinate ligand and two coordinate phosphorus has been synthesized from the reaction of heteroleptic chlorosilylene LSiCl (1), TripPCl2 (Trip = 2, 4, 6- i Pr3 C6 H2 ) and KC8 in a 1 : 1 : 3 ratio. The same reaction in a 1 : 2 : 6 ratio in the presence of one equivalent of 18-crown-6 ether affords the 1, 3-diphospha-2-silaallyl anion.